THE INFLUENCE OF JASA MARGA SOCIAL AND ENVIRONMENTAL RESPONSIBILITIES ON ACHIEVING SUSTAINABLE DEVELOPMENT GOALS IN INDONESIA - Rizqi Aina; Ratih Hendayani (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2023)
Sustainable Development Goals are increasingly becoming a concern for several countries, that according to United Nations they need to achieve the 17 goals of these SDGs by 2030. In achieving the SDGs all parties who have an interest need to collaborate, namely the stakeholders of the SDGs where one of them is a business actor. Jasa Marga as a largest toll road company in Indonesia has realized that SDGs are an important aspect of its business process. The purpose of this study was to determine the influence of corporate social and environmental responsibility on the achievement of the SDGs. This study will analyze 134 samples of Jasa Marga employee using the Structural Equation Modeling (SEM) analysis method, namely Partial Least Square (PLS). The results of the study show that there is a positive relationship between social responsibilities and environmental responsibilities of Jasa Marga in supporting the achievement of SDGs in Indonesia and the existence of organizational effectiveness which mediates the company's social responsibilities and environmental responsibilities with the achievement of SDGs and it is also found that organizational effectiveness can support the achievement of SDGs. Thus, this study can show that there is a positive influence from the company's social responsibilities and environmental responsibilities in supporting the achievement of SDGs in a region. This study has a limitation so in addition, further study can also collect more diverse data and increase the population.